Mapeamento e proposta de conexão de fragmentos florestais em Santa Maria (RS) - Silva, Natália Huber da (2015)
Recent studies which feature the urban area land use mapping Santa Maria do not have tree-canopy cover differentiation, as Deciduous Atlantic Forest and exotic tree plantations - mostly of Pinus sp. and Eucalyptus sp.. Thus, the study main objective is to carry out a forest fragments analysis of the Santa Maria‟s District Headquarters, seeking a connection proposal to maintain the faunistic genetic flux in a city neighborhood. In order to choose the neighborhood were identified and classified forest fragments in exotic and native, through the manual vectorization a scale of approximately 1: .2000, through Google Earth Pro₢ software with image of Digital Globe₢ satellite, from April 2014. This vectorization was applied to the map of the Headquarters District land use, getting big differences compared to the automatic classification of Maxver₢ in Landsat 8₢, from November, 2014. Through population data provided by the City Hall it was possible calculate a Tree-canopy Cover Index (of Deciduous Forest) per capita. Also, metric parameters as area, circularity and the distance between the fragments were regarded as priorities, respectively, and each one with eliminating character. After tabulating of fragments metrics, through the import of vectorized files for ArcGIS 10.0₢, was established the neighborhood in which the connection proposition was made, and this was carried out another map of use of neighborhood land with Digital Globe₢ image. For connecting proposal of forest fragments were used structural interventions in roads and reforestation areas with native or not invasive exotic species as mitigation measures to fragmentation. These structures are already in use at international, national and state level and most are easy to install or adapt to use of faunal biodiversity. As a result it was found that the city has a tree-canopy cover index per capita reasonably high, with an average of 47.6 m² / inhab. But, dividing the city in Administrative Regions, there are greater differences into this index, that declines to 0.01 m² / inhab. in western region of the city. Based on data like these, it was found that the agricultural practice deforests more than civil constructions in the city, in moving forward about Permanent Preservation Areas. As well, it was observed within the study area that the more distant the remaining fragments of Atlantic Forest are located of its area source, scarcer and smaller they are. Furthermore, it was statistically demonstrated that in urban areas, larger fragments tend to have a lower circularity. The neighborhood that was chosen by the metric mentioned was the Km 3, which houses a large remaining fragment of the Plateau Escarpment. This presented about half of its area covered by fragments of native species and, by having a low population index of 2,700 inhabitants to more than two million square meters of rainforest, has about 660 square meters of tree-canopy native cover per inhabitant, a very high rate for an embedded area in the urban perimeter.